ANALISIS FAKTOR-FAKTOR PENENTU PERSISTENSI LABA - Nuraini, Mety; Purwanto, Agus (Diponegoro Journal of Accounting, 2014)
This study aims to examine the persistent of cash flow, accruals (TACC) and accruals reliability such as as net financial accruals (ΔFIN), non-cash working capital accruals (ΔWC), and non-current operating accruals (ΔNCO) to the earnings persistence. In addition this study also examine whether leverage, operation cycles, and size have relationship to the earnings persistence.             The population of this study is a manufacturing company listed on the Indonesia Stock Exchange (IDX) of years 2008-2012. Samples were selected using proposive sampling method. Data were analyzed by multiple regression analysis with SPSS 21 application.             The result of this study indicate that the TACC is less persistence than cash flows. The persistence of accrual components is positively associated with the reliability of those components. However, non-cash working capital accruals (ΔWC) did not have significant influence to earnings persistence and the least reliable accrual component has the greatest persistence. In addition, operation cycle and size of company have positive relationship to earnings persistence, while the leverage did not have significant influence to earnings persistence.